Synthetic nanoemulsion resembling a protein-free model of 7-ketocholesterol containing low density lipoprotein: In vitro and in vivo studies - Favero, Giovani Marino; Maranhão, Raul Cavalcante; Maria, Durvanei Augusto; Levy, Débora; Bydlowski, Sérgio Paulo (My University, 2010)
7-ketocholesterol (7-KC) differs from cholesterol by a functional ketone group at C7. It is an oxygenated cholesterol derivative (oxysterol), commonly present in oxidized low-density lipoprotein (LDL). Oxysterols are generated and participate in several physiologic and pathophysiologic processes. For instance, the cytotoxic effects of oxidized LDL have been widely attributed to bioactive compounds like oxysterols. The toxicity is in part due to 7-KC. Here we aimed to demonstrate the possibility of incorporating 7-KC into the synthetic nanoemulsion LDE, which resembles LDL in composition and behavior. This would provide a suitable artificial particle resembling LDL to study 7-KC metabolism. We were able to incorporate 7-KC in several amounts into LDE. The incorporation was evaluated and confirmed by several methods, including gel filtration chromatography, using radiolabeled lipids. The incorporation did not change the main lipid composition characteristics of the new nanoparticle. Particle sizes were also evaluated and did not differ from LDE. In vivo studies were performed by injecting the nanoemulsion into mice. The plasma kinetics and the targeted organs were the same as described for LDE. Therefore, 7-KC-LDE maintains composition, size and some functional characteristics of LDE and could be used in experiments dealing with 7-ketocholesterol metabolism in lipoproteins.
Keywords: Emulsion; LDL; LDE; 7-ketocholesterol; Oxidized LDL; oxysterol